Rolʹ mass-medijnyh precedentnyh tekstov v formirovanii sovremennogo russkogo slenga - Balašova, Lûbovʹ V. (Stylistyka, 2010)
The author analyses the usage of mass media precedent texts in modem Russian slang, defines the main thematic groups, which regularly enrich the slang and their conceptual filling and singles out the main functions of mass media precedent phenomena in the slang.